2020
DOI: 10.21886/2308-6424-2020-8-3-85-96
|View full text |Cite
|
Sign up to set email alerts
|

Does botulinum therapy affect the urine microbiome of patients with neurogenic bladder? Metagenomic sequencing results

Abstract: Введение. Реорганизация микробиома мочи больных нейрогенным мочевым пузырем играет важную роль в патогенезе инфекции мочевыводящих путей (ИМп). сведения о составе мочевого микробиома при нейрогенной дисфункции нижних мочевыводящих путей (НДНМп) ограничены, в частности, неизвестно, как на него влияют различные виды терапии НДНМп. Цель исследования. Оценить влияние инъекций ботулинического токсина на микробиом мочи больных НДНМп. Материалы и методы. Образцы мочи были взяты у шести пациентов с НДНМп (четырёх женщ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…All the urine studies had moderate risk of bias. The studies did not account for confounding variables and the extent of injury in the study populations were not sufficiently described [23][24][25][26][27][28] (Supplementary Table 1).…”
Section: Spinal Cord Injury and Urinary Tract Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…All the urine studies had moderate risk of bias. The studies did not account for confounding variables and the extent of injury in the study populations were not sufficiently described [23][24][25][26][27][28] (Supplementary Table 1).…”
Section: Spinal Cord Injury and Urinary Tract Microbiomementioning
confidence: 99%
“…Their longitudinal analysis showed that the microbiome changed with the onset of probiotics or the presence of symptomatic UTI but reverts to baseline microbiome profile. Philippova et al [26] studied the effect of intradetrusor botulinum in 6 adults (2 males, 4 females) with SCI from trauma or spina bifida. The intervention decreased the occurrence of symptomatic UTI after 6 months of observation.…”
Section: Spinal Cord Injury and Urinary Tract Microbiomementioning
confidence: 99%